Increasing antibiotic resistance among urinary tract isolates. Issue 5 (1st May 2003) - Ladhani, S; Gransden, W
Abstract : A five year retrospective study was performed to identify organisms isolated from the urinary tract of 2815 children in the community and 1314 children with underlying renal problems and their antimicrobial susceptibilities. Isolates from children in the latter group were generally more resistant to commonly used antibiotics. In particular, up to a third of E coli isolates from children in the community and almost two thirds of E coli isolates from children with underlying renal disease may be resistant to trimethoprim.